Inkonsistensi Kebijakan Formulasi Pertanggungjawaban Pidana Korporasi Dalam Peraturan Perundang-undangan - Yoga Nugroho; Nyoman Serikat Putra Jaya (Criminal of Law Department, Faculty of Law, Pattimura University, 2021)
The purpose of this study is to analyze the inconsistency of the formulation of corporate criminal liability in the Corruption Act and Narcotics Law, and to analyze the consequences of the formulation inconsistency. This research method uses normative legal research and library research, then analyzed by qualitative methods. The result of this research is that there have been inconsistencies/inconsistencies related to the formulation of corporate criminal liability against the Corruption Act and the Narcotics Law. It can be seen that there are differences in formulating norms regarding corporate responsibility, so that it can lead to disparities in judges' decisions in passing verdicts and disharmony of arrangements that can hinder the law enforcement process.